2019
DOI: 10.1088/1742-6596/1234/1/012073
|View full text |Cite
|
Sign up to set email alerts
|

Anti-neoplastic effect of epigallocatechin gallate on breast cancer cells through glucose metabolism

Abstract: Breast cancer (BC) is the primary cause of women cancer death, which could be prevented by EGCG that has been recently shown several health properties included anti-cancer, however the mechanism underpinning still poorly understood. In this study, several biological activities of both MCF7 and MDA-MB-231 cells were evaluated in response to EGCG. Cell viability and the role of Akt and AMPK inhibitor molecules, and sodium pyruvate on this viability, apoptosis, metastasis, and interestingly regulation of glucose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
2
0
1
Order By: Relevance
“…To characterize the EVs release, serum-starved TNBC-derived MDA-MB-231 cells were cultured in the presence or absence of 30 µM EGCG for 48 h. A concentration documented to not alter MDA-MB-231 cell viability [ 45 47 ]. Conditioned media was next collected, and EVs were isolated as described in the Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…To characterize the EVs release, serum-starved TNBC-derived MDA-MB-231 cells were cultured in the presence or absence of 30 µM EGCG for 48 h. A concentration documented to not alter MDA-MB-231 cell viability [ 45 47 ]. Conditioned media was next collected, and EVs were isolated as described in the Methods section.…”
Section: Resultsmentioning
confidence: 99%
“…Ademais, pesquisas comprovaram que esse elemento obstaculiza o desenvolvimento de células TNBC por meio da inoperância do caminho de sinalização de β-catenin 43 . Igualmente, mostra ações anti-migração e pró-apoptose por meio do estímulo de caspases -3/7 e normatização de Bax 44 .…”
Section: Epigalocatequina Galato (Egcg)unclassified
“…Furthermore, studies have demonstrated that EGCG inhibits the growth of TNBC cells through the inactivation of the β-catenin-signaling pathway [ 153 , 154 ]. Remarkably, this antioxidant exhibits anti-migration and pro-apoptosis activities through the activation of caspases 3/7 and upregulation of Bax [ 155 ]. Moreover, the combination with curcumin and α-tocopheryl succinate into polystyrene–polysoyaoil–diethanolamine nanoparticles demonstrated to inhibit tumor growth and reduce toxicity when compared with single-drug chemotherapy [ 156 ].…”
Section: Antioxidants and Breast Cancermentioning
confidence: 99%